The Effect of Liraglutide on Lung Cancer and Its Potential Protective Effect on High Glucose-Induced Lung Senescence and Oxidative Damage - Zhiyan Pu; Yanxia Yang; Shuanghong Qin; Xiaojuan Li; Can Cui; Weiyu Chen (Frontiers in Bioscience-Landmark, 2023)
Background: Lung cancer is a malignant disease with high morbidity and mortality. Lung cancer and diabetes are closely related, and diabetic patients with lung tumors are common in clinical practice. Liraglutide, a glucagon-like peptide-1 receptor (GLP-1R) agonist, is commonly used in the treatment of type 2 diabetes. In this study, we examined the effect of liraglutide on lung cancer and its potential protective effect on high glucose-induced lung aging. Methods: Indirect mmunofluorescence was done to assess the expression levels of p-AKT, ki67, Caspase3, Bax and PI3K. Western blotting was conducted to determine the expression levels of BAX, BCL2, Caspase9, E-cadherin, N-cadherin, PI3K, AKT and vimentin. Cell viability, cell cycle and cell apoptosis were evaluated by colony formation, CCK-8 assay and flow cytometry. Immunohistochemistry was performed to evaluate the expression of Nf-κb, p15, p16, p21 and SMA in vivo. Besides, a high glucose-induced lung cell injury model was established to evaluate the effect of liraglutide on lung aging and oxidative damage. Sa-β-gal staining was used to assess cellular/ tissue senescence. Cell senescence-related markers (p16, p21 and p53 ) were determined by Western-blot analysis. Results: The proliferation, cell cycle, migration of lung cancer cells were significantly inhibited after treatment with liraglutide compared to control group (p < 0.05). Furthermore, Liraglutide inhibited the epithelial–mesenchymal transition process of lung cancer cell compared to control group (p < 0.05). Liraglutide also suppressed the proliferation of lung cancer in vivo. Besides, the BEAS-2B cell senescence induced by high glucose was significantly alleviated after treatment with liraglutide compared with control group (p < 0.05). The lung aging and endoplasmic reticulum stress was significantly suppressed after liraglutide treatment. Conclusions: This work indicates that liraglutide could inhibit lung cancer cell proliferation in vitro and in vivo. In addition, liraglutide exhibited anti-aging effects in vivo and in vivo. The current work has important implications for the treatment of patients with diabetes and lung cancer.